2021
DOI: 10.1021/acs.jpca.1c01650
|View full text |Cite
|
Sign up to set email alerts
|

Early Chemistry of Nicotine Degradation in Heat-Not-Burn Smoking Devices and Conventional Cigarettes: Implications for Users and Second- and Third-Hand Smokers

Abstract: Nicotine exposure results in health risks not only for smokers but also for second- and third-hand smokers. Unraveling nicotine’s degradation mechanism and the harmful chemicals that are produced under different conditions is vital to assess exposure risks. We performed a theoretical study to describe the early chemistry of nicotine degradation by investigating two important reactions that nicotine can undergo: hydrogen abstraction by hydroxyl radicals and unimolecular dissociation. The former contributes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
3
6
1
Order By: Relevance
“…Overall rate coefficients from C1, C3, and C6 are 3.79 × 10 −11 , 3.10 × 10 −11 , and 1.28 × 10 −11 cm 3 molecule −1 s −1 , respectively. Our predictions here are somewhat different from those by Chavarrio Canãs et al, 19 who included torsional anharmonicity in their variational TST calculations and obtained an overall rate coefficient of 5.76 × 10 −11 cm 3 molecule −1 s −1 (1.93 × 10 −11 , 3.41 × 10 −11 , and 4.18 × 10 −12 cm 3 molecule −1 s −1 from C1, C3, and C6). The differences here are still within the uncertainties.…”
Section: ■ Results and Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Overall rate coefficients from C1, C3, and C6 are 3.79 × 10 −11 , 3.10 × 10 −11 , and 1.28 × 10 −11 cm 3 molecule −1 s −1 , respectively. Our predictions here are somewhat different from those by Chavarrio Canãs et al, 19 who included torsional anharmonicity in their variational TST calculations and obtained an overall rate coefficient of 5.76 × 10 −11 cm 3 molecule −1 s −1 (1.93 × 10 −11 , 3.41 × 10 −11 , and 4.18 × 10 −12 cm 3 molecule −1 s −1 from C1, C3, and C6). The differences here are still within the uncertainties.…”
Section: ■ Results and Discussioncontrasting
confidence: 99%
“…Figure 1 shows the relative energies for intermediates, transition states, and products and the rate coefficients for these product channels (complete list in Table S1). The , 19 and that of −13.4 kJ/mol for HAA-TS1 at the M06-2X/6-311+G(d,p) level by Borduas et al 12 Weak PRCs, with energies ∼5 and ∼9 kJ/mol below nicotine + OH, are also identified to have weak hydrogen bonds between C1−H and OH as in previous studies. 12,19 The overall rate coefficient at 298 K, 8.37 × 10 −11 cm 3 molecule −1 s −1 , agrees excellently with the experimental value of (8.38 ± 0.28) × 10 −11 cm 3 molecule −1 s −1 by Borduas et al 12 The dominance of HAA channels is obvious.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 3 more Smart Citations